(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article examines the impact of structured learning ( structured The impact of training and organizational discipline on employee performance is explored. Based on theoretical approaches (human capital theory, social learning theory) and the results of large reviews and meta-analyses, it is shown that well-designed training programs consistently improve knowledge, behavior, and organizational outcomes, while discipline acts as a moderator and direct predictor of performance. Recommendations are provided for designing training programs, implementing disciplinary practices, and evaluating the effects using a multi-level evaluation framework.